Vitamin D in regulating immune response in patients with recurrent pregnancy loss: a case-control study - Khudhair, Hasan Abd Ali (Medical Journal of Indonesia, 2025)
BACKGROUND Recurrent pregnancy loss (RPL) is linked to lower vitamin D levels and altered immune responses, though unclear mechanisms. This study aimed to identify the effect of vitamin D on the balance between interleukin (IL)-10/IL-17A in women with RPL. METHODS This case-control study was conducted at the Bint Al-Huda Teaching Hospital, Thi-Qar Governorate, Iraq, from August 2022 to March 2023. Three study groups were included: RPL (47 women), non-aborted pregnant (40 women), and control (38 women). The sera concentrations of IL-17A, vitamin D, and IL-10 had been quantitatively detected using ELISA. SPSS was used for statistical analysis. RESULTS Women with RPL had significantly lower vitamin D levels (19.6 ng/ml) and higher IL-17A levels (35.66 ng/l) than the non-aborted pregnant (23.46 ng/ml, 24.04 ng/l) and control groups (25.69 ng/ml, 19.87 ng/l). IL-10 levels were substantially depleted in the RPL group (3.96 pg/ml), leading to a statistically lower IL-10/IL-17A ratio (0.19) than in the non-aborted pregnant (0.58) and control (1.60) groups. Regression analysis revealed a valuable positive association between vitamin D and IL-17A in all groups and between vitamin D and IL-10/IL-17A ratio in RPL and control groups. Vitamin D was also significantly associated with IL-10 in the non-aborted pregnant group. However, no statistical relationship was reported between vitamin D and IL-10 levels in the RPL and control groups. CONCLUSIONS Increased IL-17A and decreased IL-10 contributed to unexplained RPL. The IL-10/IL-17A ratio predicted endometrial function, and vitamin D affects these cytokines, potentially reducing inflammation.